2018
DOI: 10.1016/j.omto.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal Effect in Non-injected Tumors Achieved with Cytokine-Armed Oncolytic Adenovirus

Abstract: Cancer treatment with local administration of armed oncolytic viruses could potentially induce systemic antitumor effects, or the abscopal effect, as they self-amplify in tumors, induce danger signaling, and promote tumor-associated antigen presentation. In this study, oncolytic adenovirus coding for human tumor necrosis factor alpha (TNF-α) and interleukin-2 (IL-2) Ad5/3-E2F-d24-hTNF-α-IRES-hIL-2 (also known as [a.k.a.] TILT-123) provoked antitumor efficacy in tumors that were injected with Ad5/3-E2F-d24-hTNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…A comparable effect can be achieved by locally applied oncolytic therapies, either viruses devoid of virulence factors [354], or synthetic amino acid oligomers that mimic host-defense peptides and disrupt cellular membranes to cause immunogenic lysis of tumor cells [355]. Like radiotherapy, oncolytics convert the tumor to an in situ vaccine [356] and can also elicit abscopal effects [357, 358]. On the other hand, several immunomodulatory strategies are being developed according to the principles of precision medicine and target specific pathways and/or cells of the TME.…”
Section: Therapeutic Immunomodulationmentioning
confidence: 99%
“…A comparable effect can be achieved by locally applied oncolytic therapies, either viruses devoid of virulence factors [354], or synthetic amino acid oligomers that mimic host-defense peptides and disrupt cellular membranes to cause immunogenic lysis of tumor cells [355]. Like radiotherapy, oncolytics convert the tumor to an in situ vaccine [356] and can also elicit abscopal effects [357, 358]. On the other hand, several immunomodulatory strategies are being developed according to the principles of precision medicine and target specific pathways and/or cells of the TME.…”
Section: Therapeutic Immunomodulationmentioning
confidence: 99%
“…However, this route has one major shortcoming in that it focuses on treatment of non-metastatic accessible tumors. Even if an abscopal effect has been reported in murine models, only limited data of distant effects are available in human medicine 35 – 40 . To overcome the drawback of the intratumoral route, the intravenous route has been considered 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained from two syngeneic mouse tumor models revealed that adenovirus coding for CD40L mediated multiple antitumor effects including oncolysis, apoptosis, induction of T-cell responses, and upregulation of Th1 cytokines [123]. Another vector, Ad5/3-E2F-d24-hTNF-a-IRES-hIL-2, induced abscopal effects in non-injected tumors thus revealing systemic antitumor efficacy [124]. Type I IFN signaling was required for the induction of antigen-specific CD8+ T cell responses in the gut mucosa following intra-muscular adenovirus vector vaccination [125].…”
Section: Comparison Of Ndv To Other Ovsmentioning
confidence: 99%